Effect of Ulnar Collateral Ligament Reconstruction on Pitch Accuracy, Velocity, and Movement in Major League Baseball Pitchers. Issue 12 (16th December 2020) - McKnight, Braden; Heckmann, Nathanael D.; Chen, Xiao T.; Hindoyan, Kevork; Hill, J. Ryan; Goldbeck, Graham; Omid, Reza; Hatch, George F. "Rick"; Charlton, Timothy P.
Background: Ulnar collateral ligament (UCL) reconstruction is frequently performed on Major League Baseball (MLB) pitchers. Previous studies have investigated the effects of UCL reconstruction on fastball and curveball velocity, but no study to date has evaluated its effect on fastball accuracy or curveball movement among MLB pitchers. Purpose/Hypothesis: The primary purpose of this study was to determine the effects of UCL reconstruction on fastball accuracy, fastball velocity, and curveball movement in MLB pitchers. Our hypothesis was that MLB pitchers who underwent UCL reconstruction would return to their presurgery fastball velocity, fastball accuracy, and curveball movement. The secondary purpose of this study was to determine which factors, if any, were predictive of poor performance after UCL reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: MLB pitchers who underwent UCL reconstruction surgery between 2011 and 2012 were identified. Performance data including fastball velocity, fastball accuracy, and curveball movement were evaluated 1 year preoperatively and up to 3 years of play postoperatively. A repeated-measures analysis of variance with a Tukey-Kramer post hoc test was used to determine statistically significant changes in performance over time. Characteristic factors and presurgery performance statistics were compared between poor performers (>20% decrease in fastball accuracy) and non—poor performers. Results: We identified 56 pitchers with a total of 230, 995 individual pitches for this study. After exclusion for lack of return to play (n = 14) and revision surgery (n = 3), 39 pitchers were included in the final analysis. The mean presurgery fastball pitch-to-target distance was 32.9 cm. There was a statistically significant decrease in fastball accuracy after reconstruction, which was present up to 3 years postoperatively ( P = .007). The mean presurgery fastball velocity of 91.82 mph did not significantly change after surgery ( P = .194). The mean presurgery curveball movement of 34.49 cm vertically and 5.89 cm horizontally also did not change significantly ( P = .937 and .161, respectively). Conclusion: Fastball accuracy among MLB pitchers significantly decreased after UCL reconstruction for up to 3 years postoperatively. There were no statistically significant differences in characteristic factors or presurgery performance statistics between poor and non--poor performers.